2015
DOI: 10.1002/chem.201503359
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regioselective Palladium‐Catalyzed Carboxylation of Allylic Alcohols with CO2

Abstract: Various allylic alcohols were carboxylated in the presence of a catalytic amount of PdCl2 and PPh3 using ZnEt2 as a stoichiometric transmetalation agent under a CO2 atmosphere (1 atm). This carboxylation proceeded in a highly regioselective manner to afford branched carboxylic acids predominantly. The β,γ-unsaturated carboxylic acid thus obtained was successfully converted into an optically active γ-butyrolactone, a known intermediate of (R)-baclofen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 74 publications
(24 reference statements)
1
32
0
Order By: Relevance
“…48 In all cases analyzed, α-branched carboxylic acids were exclusively obtained regardless of whether linear or α-branched allyl alcohols were utilized. The authors demonstrated the utility of this protocol by promoting a one-pot carboxylation using simple aldehydes as starting precursors.…”
Section: Direct Catalytic Carboxylation Of C–heteroatom Bonds With Co2mentioning
confidence: 95%
“…48 In all cases analyzed, α-branched carboxylic acids were exclusively obtained regardless of whether linear or α-branched allyl alcohols were utilized. The authors demonstrated the utility of this protocol by promoting a one-pot carboxylation using simple aldehydes as starting precursors.…”
Section: Direct Catalytic Carboxylation Of C–heteroatom Bonds With Co2mentioning
confidence: 95%
“…[4] Tsuji and co-workers applied [NiCl 2 (PPh 3 ) 2 ]f or the carboxylation of more inert aryl and vinyl chlorides under aC O 2 pressure of 1atm at room temperature. [5] Later,avariety of surrogates,i ncluding sulfonates, [6] ester derivatives, [7] allylic alcohols, [8] and ammonium salts [9] were devised to complement the reaction scope. Notably,a ll of these systems require stoichiometric metal reagents based on Et 2 Zn, Mn, or Zn powder as reducing agents (Scheme 1a).…”
mentioning
confidence: 99%
“…[7] Oxidative addition of the allylic C (sp 3 )À H bond to I affords η 3 -allylcobalt(III) intermediate II, which is tautomerized to η 1 -allylcobalt(III) intermediate III with the assistance of the oxygen atom in the Xantphos ligand. The cobalt atom should be located at the terminal position to avoid steric repulsion between the bulky Xantphos ligand and an alkyl substituent (similar to nucleophilic η 1 -allylpalladium species [13,14] ). Subsequently, reductive elimination of methane from III leads to a low-valent allylcobalt(I) species IV, and CÀ C bond formation with the ketone moiety occurs to produce cobalt(I) alkoxide V. In this step, the nucleophilic addition takes place from IV rather than IV' to avoid steric repulsion between the bulky Xantphos ligand and the phenyl substituent, affording syn-oriented intermediate V. Transmetallation of V with AlMe 3 furnishes the branched aluminum alkoxide VI and regenerates I. Alkoxide VI is converted into product 2 a upon workup.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%